Social determinants in health and mental well-being among out-patients - Moreno-Lacalle, Rainier C.; Ducusin, Pilar Bianca Mae G.; Suma-il, Rayvine B.; Tiu, Lana Stephanie A.; Manantan, Kyla Dee; Borromeo, Karyle Myara E.; Cruz, Amanda Nicole N.; Landagora, Romeo Benedict; Nerona, Chad Allen M.; Edualino, Christan James R. (Intelektual Pustaka Media Utama, 2025)
Social determinants are crucial in shaping mental well-being, yet their specific impact within diverse cultural contexts like the Philippines remains underexplored. This study investigated the influence of social determinants on mental well-being among out-patients with mental health conditions. A retrospective cross-sectional design was used, analyzing existing health records (n = 21,813) from 2019 to 2024 and survey questionnaires (n = 89) from three psychiatric institutions. Social determinants were classified as proximal or distal, and mental well-being was assessed using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). Results showed that participants generally reported a high level of mental well-being. Regression analysis revealed that while proximal social factors collectively explained the largest variance in well-being (28.6%), they were not statistically significant predictors as a group. Conversely, specific distal factors-notably birth order (p<0.010), parental marital status (p<0.017), and a history of family sexual abuse (p<0.033)-were significant individual predictors. This research provides novel evidence on the application of the proximal-distal framework in a Filipino context, uniquely demonstrating that while broad social categories are influential, specific familial and life-course events are more direct predictors of mental well-being. The findings underscore the need for culturally-sensitive, targeted interventions that address both broad environmental factors and specific individual circumstances to promote health equity.